The Effectiveness on job Training Program at the Manpower Department in Reducing Unemployment Rates - Langlang Buana, Prammudya; Purwanti, Dian; Basori, Yana Fajar FY. (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Sukabumi, located in West Java Province, faces serious challenges related to high unemployment rates. This phenomenon is a complex issue that needs to be addressed. One of the solutions that have been proposed and implemented in various regions, including Sukabumi, is the Job Training Program. This research aims to determine the effectiveness of the job training program conducted by the Manpower Office in reducing the unemployment rate in Sukabumi. The research method uses a qualitative approach with a descriptive method. It employs the theory of the "Four Accuracies" by Richard Matland, which has been developed into "Five Accuracies" by Dian Purwanti. The Job Training Program in Sukabumi is still not optimal and faces many challenges, especially in the training provided. There is a lack of clarity after completing the program, and the job opportunities available do not match the market needs in Sukabumi. This program should collaborate with the job fair programs provided by the Sukabumi Manpower Office to make job training more effective and aligned with the current job market needs. Additionally, there is no monitoring of participants who have completed the Job Training Program, which should be carried out by the Sukabumi Manpower Office to assess the effectiveness of the program in reducing unemployment rates in Sukabumi.